Sistem Informasi Beasiswa Mahasiswa Berprestasi Wonogiri Berbasis Mobile - RR. Hajar Puji Sejati; Albertus Novvidi Setyo Setyo (Universitas Islam Raden Rahmat, Malang, 2024)
Scholarships are financial assistance to support education that is often given to students, both for outstanding students and students who are economically disadvantaged. The distribution of tuition assistance generally aims to support underprivileged students so that they can attend education despite their lack of financial conditions. The Wonogiri Regency Government itself has prepared a scholarship program for outstanding students to boost human resource in the Wonogiri Regency. In Wonogiri Regency itself, many outstanding students need scholarship assistence, but they still have difficulty getting information about the program due to the lack of information media that has not been supported. The research method used is teh rapid application development (RAD) method. This research aims to design an Android-based scholarship information system application that is expected to help make it easier for students to get information and register for scholarships online without having to come to the registration location.